Vertebral Bone Mineral Density, Vertebral Strength, and Syndesmophyte Growth in Ankylosing Spondylitis: The Importance of Bridging. Issue 8 (27th June 2022) - Tan, Sovira; Bagheri, Hadi; Lee, David; Shafiei, Ahmad; Keaveny, Tony M.; Yao, Lawrence; Ward, Michael M.
Abstract : Objective: To examine the relationship between vertebral trabecular bone mineral density (tBMD), vertebral strength, and syndesmophytes in patients with ankylosing spondylitis (AS) using quantitative computed tomography (QCT). Methods: We performed QCT of the spine to measure syndesmophytes and tBMD in 5 vertebrae (T11–L3) in 61 patients with AS. Finite element analysis was performed to measure vertebral strength in compressive overload, including in trabecular and cortical compartments. In cross‐sectional analyses, we examined associations of syndesmophyte height with tBMD and vertebral strength in each vertebra. In 33 patients followed up for 2 years, we investigated whether baseline tBMD and vertebral strength predicted syndesmophyte growth in the same vertebra, and vice versa. Results: In the cross‐sectional analyses, 126 vertebrae had bridging, 77 vertebrae had nonbridging syndesmophytes, and 83 vertebrae had no syndesmophytes. There were strong inverse associations between syndesmophyte height and tBMD, total strength, and trabecular strength only among bridged vertebrae. In the longitudinal analysis, nonbridged vertebrae with low tBMD (adjusted β = –0.01 [95% confidence interval (95% CI) –0.019, –0.0012]) and low strength (adjusted β = –0.0003 [95% CI –0.0004, –0.0002]) had more syndesmophyte growth over time. Similar associations were absent among bridged vertebrae. Conversely, vertebrae with bridging at baseline had a significant loss in percent tBMD over time (adjusted β = –0.001 [95% CI –0.0017, –0.0004]). Conclusion: Associations between syndesmophytes and vertebral density and strength in AS differ between bridged and nonbridged vertebrae. Among nonbridged vertebrae, low tBMD and strength are associated with syndesmophyte growth. Bridging is associated with large subsequent losses in tBMD, possibly due to mechanical offloading.